2009
DOI: 10.3109/10611860903450023
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid modified chitosan nanoparticles for effective management of glaucoma: development, characterization, and evaluation

Abstract: In clinical practices, solution of dorzolamide hydrochloride (DH) and timolol maléate (TM) is recommended for the treatment of glaucoma. However, low drug-contact time and poor ocular bioavailability of drugs due to drainage of solution, tear turnover and its dilution or lacrimation limits its uses. In addition, systemic absorption of TM may induce undesirable cardiovascular side effects. Chitosan (CS) is a polycationic biodegradable polymer which provides sustained and local delivery of drugs to the ocular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 32 publications
4
69
1
3
Order By: Relevance
“…The size was relatively similar to another study utilizing nanoparticles in PLGA microparticles which reported a nanoparticle size of 513 nm (50) . Empty chit/TPP particles were significantly larger than chitosan particles (345.5 ± 2.5 and 40.1 ± 3 nm, respectively, p = 1.79 x 10 -8 ) and previously reported chit/TPP particles of sizes up to 226 nm (51) . This is due to the use of a higher chitosan Mw and chit/TPP ratio of 10:1 compared 4:1 (51) as these parameters have been reported to influence the particle size (52) .…”
Section: Characterization Of Chitosan-based Nanoparticlesmentioning
confidence: 87%
“…The size was relatively similar to another study utilizing nanoparticles in PLGA microparticles which reported a nanoparticle size of 513 nm (50) . Empty chit/TPP particles were significantly larger than chitosan particles (345.5 ± 2.5 and 40.1 ± 3 nm, respectively, p = 1.79 x 10 -8 ) and previously reported chit/TPP particles of sizes up to 226 nm (51) . This is due to the use of a higher chitosan Mw and chit/TPP ratio of 10:1 compared 4:1 (51) as these parameters have been reported to influence the particle size (52) .…”
Section: Characterization Of Chitosan-based Nanoparticlesmentioning
confidence: 87%
“…In in vivo rabbit studies, chitosan NPs encapsulating timolol have been shown to be more effective in lowering IOP as compared with a drug solution. 10 In another study, the subconjuctival administration of microspheres encapsulating the drug exhibited sustained drug release for up to 3 months in in vitro conditions. 11 Similarly, a contact lens loaded with 5% 1:1 timolol: propoxylated glyceryl triacylate NPs continued drug release for up to 1 month under in vitro conditions (Fig.…”
Section: Nanomedicinementioning
confidence: 98%
“…The combination of these properties makes polysaccharides versatile biopolymers for ocular drug delivery [71, 8489]. Drugs such as cyclosporine A (CsA) [90], dorzolamide hydrochloride [91, 92], pramipexole hydrochloride [91], acyclovir [93], 5-flurouracil [94], carteolol [92], gatifloxacin [95], betamethasone sodium phosphate [96], gene [97], pilocarpine [98], econazole nitrate [99], natamycin [100], daptomycin [89], amphotericin B [101], celecoxib [102], timolol maleate [103, 104], fluconazole [105], sodium diclofenac [106], and tropicamide [107] were loaded into nanoparticles made of polysaccharides for ocular delivery. The release of the drugs from these hydrophilic polymer nanoparticle matrices relies on various factors such as polymer hydration, solvent penetration, drug diffusion, drug dissolution, and/or polymer erosion [95].…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%